2021
DOI: 10.3390/met11111776
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fatigue Crack Growth Rate in Heat-Resistant Steel by Processing of Digital Images of Fracture Surfaces

Abstract: The micro- and macroscopic fatigue crack growth (FCG) rates of a wide class of structural materials were analyzed and it was concluded that both rates coincide either during high-temperature tests or at high stress intensity factor (SIF) values. Their coincidence requires a high level of cyclic deformation of the metal along the entire crack front as a necessary condition for the formation of fatigue striations (FS). Based on the analysis of digital fractographic images of the fatigue fracture surfaces, a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Figure 5c shows a picture of one initiation point in higher magnification. Figure 5d shows striations typical for stable fatigue crack growth [9]. The detail from the area of the final fracture (see Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 5c shows a picture of one initiation point in higher magnification. Figure 5d shows striations typical for stable fatigue crack growth [9]. The detail from the area of the final fracture (see Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The study (ibid) results showed that the proposed model achieves a classification accuracy of 93.86%. A method for the quantitative assessment of the spacing of FS was developed by (Maruschak et al, 2021). The method includes the detection of FS by binarization of the image based on the principle of local minima and rotation of the highlighted fragments of the image using the Hough transform.…”
Section: Crack Detection Based Hough Transformmentioning
confidence: 99%
“…The main factors of the degradation of heat-resistant steels operated at TPPs include high temperature and stress, supplemented by the influence of a hydrogen-inducing technological environment [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. During the long-term operation of high-and low-alloy heat-resistant steels, the carbides form and coagulate along the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%